Optimisation de la gestion des déchets ménagers dans quelques villes de l’Ouest algérien - ASNOUNE Meriem (My University, 2017)
The household wastes management stays a big challenge for developing countries in a general way in particular for Algeria. Because of the image which they clear by their quantitative and qualitative increases, wastes present a real sign of a bigger and more diversified overconsumption engendering enormous risks on the environment and, consequently, on the health of the populations. For that reason, our study permitted, and for the first time, to contribute to the study of the household wastes management in the western cities Algerian: Tiaret, Mostaganem, Tlemcen, Oran, Relizane, Sidi-Bel-Abbès, Ain Témouchent, Mascara, Saïda, Naâma and Béchar. This by highlighting their quantities of waste by inhabitant and by day, their physical, chemical and microbiological compositions, The management situation compared to other cities and profits which can be drawn in different channels recoverable (recovery, composting, anaerobic digestion and landfill), this of the one hand. One the other hand, the situation of these cities in terms of household waste management can be improved through to the study of optimization of the management of this waste, which we propose. This study enables the identification of the possible scenarios of waste treatment by proposing the lowest cost for their exploitations and by conceiving an optimal system for their management using the principle of reduction at the source, reuse, recycling, valorization and elimination (3R-VE). Among the proposed scenarios, the model of scenario 4 (mixed installations) presents a treatment system suitable and profitable household waste that could offer cities in western Algeria during the period (2011-2025) sizeable gains by composting and the recovery of recyclable materials, and other gains from the sale of electricity through anaerobic digestion and landfill with a reduction of greenhouse gas (GHG) emissions.